Analysis of User Satisfaction in Banten with Shopeepay Mobile Payment Based on E-Service Quality - Martina Rahmawati Masitoh; Rindang Matoati (International Forum of Researchers and Lecturers, 2025)
The rapid development of technology has led to innovations in various areas, including mobile payments. Mobile payments are one of the innovations in financial technology designed to facilitate online transactions. In Indonesia, there are numerous mobile payment service providers, making competition increasingly fierce. One of the popular e-wallets in Indonesia is ShopeePay, a service created by Shopee. This study aims to analyze the importance and performance levels of various electronic service quality factors and assess user satisfaction with ShopeePay. This research is a survey-based study with a sample of 100 respondents. The analysis was conducted using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) to measure the importance and performance of each ShopeePay service quality factor and the satisfaction of its users. The results show that out of 24 ShopeePay service quality factors, 13 were considered important by respondents. The average importance rating was 4.07, while the average performance rating was 3.94. This results in a harmony between importance and performance of 97%. The Customer Satisfaction Index (CSI) for ShopeePay services in the Banten area was 78.77%, placing it in the